الرشاقة الاستراتيجية ودورها في تعزيز جودة الخدمات الصحية دراسة ميدانية في المؤسسات الاستشفائية الخاصة - زينب, شطي; نهاد, الزروق; محمد عبد العزيز, مازوزي (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة إلى التعرف على أثر الرشاقة الإستراتيجية بأبعادها (الحساسية الإستراتيجية، وضوح الرؤية، المقدرات الجوهرية، اختيار الأهداف الإستراتيجية، المسؤولية المشتركة) في تعزيز جودة الخدمات الصحية في المؤسسات الاستشفائية الخاصة المتمثلة في (ابن حيان، نور، الرمال، الأمان) بولاية الوادي. ولتحقيق أهداف الدراسة والإجابة على أسئلتها واختبار فرضياتها، اعتمدت الدراسة على المنهج الوصفي التحليلي في جمع البيانات والمعطيات المتعلقة بالدارسة، حيث اشتمل مجتمع الدارسة على العاملين والمرضى، ولتحقيق ذلك استخدمنا الاستبيان كأداة لجمع بيانات الدراسة ولضمان الحصول على استجابة عالية تم توزيع 120 عينة متمثلة في الإداريين والطاقم الطبي والمرضى من المصحات الخاصة محل الدراسة، حيث تم تحليلها باستخدام مجموعة من الأساليب الإحصائية بالاعتماد على برنامج الحزم الإحصائية للعلوم الإنسانية والاجتماعية SPSS V.25. وتوصلت الدراسة الى وجود أثر ذو دلالة إحصائية عند مستوى معنوية (α≤0.05) لأبعاد الرشاقة الإستراتيجية مجتمعة على تعزيز جودة الخدمات الصحية بالمؤسسة محل الدراسة، كما أنه لا يوجد فروق ذات دلالة إحصائية في إجابات العاملين حول أثر تطبيق أبعاد الرشاقة الإستراتيجية مجتمعة على تعزيز جودة الخدمات الصحية بالمؤسسة محل الدراسة تعزي لمتغير التأمين، وأيضا توجد فروق ذو دلالة إحصائية عند مستوى معنوية (α≤0.05) بين استجابات أفراد عينة الدراسة تعزى إلى متغير العمر والمستوى التعليمي.""This study aimed to identify the impact of strategic agility with its dimensions (strategic sensitivity, clarity of vision, core capabilities, choice of strategic goals, shared responsibility)in enhancing the quality of health services in private hospital institutions represented in (Ibn Hayyan, Noor, Rimal, Aman) Wilayt El-Oued. To achieve the objectives of the study, answer its questions and test its hypotheses, the study relied on the descriptive analytical approach in collecting data and data related to the study, where the study community included employees and patients. to achieve this, we used the questionnaire as a tool to collect study data and to ensure a high response. 120 samples represented by administrators, medical staff and patients from the private sanatoriums under study were distributed, where they were analyzed using a set of statistical methods based on the statistical packages program for Humanities and Social Sciences SPSS V.25. The study found that there is a statistically significant effect at a moral level (α≤0.05) of the dimensions of strategic agility combined on enhancing the quality of health services in the institution under study, and there are no statistically significant differences in the answers of employees about the impact of applying the dimensions of strategic agility combined on enhancing the quality of health services in the institution under study due to the insurance variable, and there are also statistically significant differences at a moral level (α≤0.05) between the responses of the study sample members attributed to the variable age and educational level."
Keywords: الرشاقة الإستراتيجية، الحساسية الإستراتيجية، وضوح الرؤية، المقدرات الجوهرية، اختيار الأهداف الإستراتيجية، المسؤولية المشتركة، جودة الخدمات الصحية، المصحات الخاصة.; strategic agility, strategic sensitivity, clarity of vision, intrinsic capabilities, choice of strategic goals, shared responsibility, quality of Health Services, Private sanatoriums.